Fatty acids and bioactive compounds of the pulps and kernels of Brazilian palm species, guariroba (Syagrus oleraces), jeriva (Syagrus romanzoffiana) and macauba (Acrocomia aculeata) - Coimbra, Michelle C. [UNESP]; Jorge, Neuza [UNESP] (Wiley-Blackwell, 2012)
BACKGROUND: Bioactive compounds are capable of providing health benefits, reducing disease incidence or favoring body functioning. There is a growing search for vegetable oils containing such compounds. This study aimed to characterize the pulp and kernel oils of the Brazilian palm species guariroba (Syagrus oleracea), jeriva (Syagrus romanzoffiana) and macauba (Acrocomia aculeata), aiming at possible uses in several industries.RESULTS: Fatty acid composition, phenolic and carotenoid contents, tocopherol composition were evaluated. The majority of the fatty acids in pulps were oleic and linoleic; macauba pulp contained 526 g kg(-1) of oleic acid. Lauric acid was detected in the kernels of all three species as the major saturated fatty acid, in amounts ranging from 325.8 to 424.3 g kg(-1). The jeriva pulp contained carotenoids and tocopherols on average of 1219 mu g g(-1) and 323.50 mg kg(-1), respectively.CONCLUSION: The pulps contained more unsaturated fatty acids than the kernels, mainly oleic and linoleic. Moreover, the pulps showed higher carotenoid and tocopherol contents. The kernels showed a predominance of saturated fatty acids, especially lauric acid. The fatty acid profiles of the kernels suggest that these oils may be better suited for the cosmetic and pharmaceutical industries than for use in foods. (C) 2011 Society of Chemical Industry
Keywords: Tocopherols; Carotenoids; Phenolic compounds; Syagrus oleracea; Syagrus romanzoffiana; Acrocomia aculeata